Left ventricular remodeling in rugby is a physiological adaptation to exercise: a pilot study conducted with high-level athletes - Rato, N. D.; Richards, J. (Sport Sciences for Health, 2022)
Purpose Literature examining left ventricular (LV) structural adaptations to combined strength and endurance training is inconsistent. Rugby is a sport that combines these two exercise modalities, both during training and match play. This study aimed to explore differences in LV structure between high-level rugby players and untrained controls. Body composition analysis was performed to determine the most appropriate indexing variable for LV mass (LVM) and understand if increases in LV represent either a training-related physiological adaptation or reflect the groups` anthropometric differences.